Situational Leadership Skills of Foundation Heads in Human Resource Development for Early Childhood Education - Matinul Haq, Ahmad; Roesminingsih, Erny (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2024)
This scientific article was written with the aim of analyzing and studying situational leadership skills that lead to the development of human resources in early childhood education institutions. This scientific article research method uses a systematic literature review with the PRISMA (Preferred Reporting Items For Systematic Review and Meta-analysis) model by implementing complete and detailed steps to conduct a literature review of journal articles. In this case, a literature search was carried out both in the form of national literature and international literature using the Scoopus, Emerald, and Google Scholar databases. In the initial stages of searching for articles, 150 articles were identified which were identified, then filtered or filtered and produced 85 articles. Then do the feasibility or eligibility and produce 45 articles. Then the last stage is carried out by producing as many as 22 articles. The results of this scientific article are that human resource development in early childhood education institutions or PAUD can be effective and efficient if it has been managed properly by the head of the foundation. There are 4 (four) skills which are the basic styles related to situational leadership theory, namely telling, selling, participating, and delegating. Ranging from leadership skills to the use of diagnostic skills, flexibility, and partnerships in an effort to maximize strategic steps in human resource development which include school management training, performance training, career training, and welfare training.